ISLAMIC RELIGIOUS EDUCATION VALUES IN THE ANIMATED FILM RIKO SEASON 3 - Farhana Farhana; Akil Akil; Jaenal Abidin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
The issue of moral decadence is still a trending among the public, especially in the world of education, this is evidenced by the many cases of bullying, brawls, violence between students and so on which are carried out by students. Therefore, the world of education is expected to be the driving force for minimizing these problems, even though in fact the problem is not only the duty and authority of the world of education, but also the duties and responsibilities of the collective. Education streamlines the learning process to foster and develop religious potential so as to influence attitudes or behavior by teaching about Islamic beliefs. The form of efforts to make the learning process effective is through animated film learning media. One of the animated films used is the animated film Riko which was released on November 9 2020 and aired on YouTube. This research method uses the literature method (Library Study) and a qualitative type of approach. This study takes 5 episodes of Riko's animation as a data source. Data collection and data analysis techniques used are documentation techniques and content analysis. The results of this study indicate that there are values ​​of Islamic religious education in the animated film Riko, namely the value of Aqidah education, the value of Sharia or Ibdah education, and the value of moral education. The implication of this research is that society understands and understands that the problem of moral decadence is not only the responsibility of education, but it is our shared duty and responsibility between education and society to unite in overcoming these problems.